Determining factors affecting sales performance: the effect of experience, competitors, level of knowledge and communication skill including of technological assistance - Azit, Azizan; Mazita, Mokhtar; Ida Rizyani, Tahir; Wan Khairul Anuar, Wan Abd Manan; Shamsudin, Norazidah
Key of sales performance affected depends on sales managers. This is because if a factor is affected can improve the profits of company and can improve the productivity the sales managers. The most factors affected sales performance of sales performance can give positive impact for sales managers. The objective of study to find the factors affected sales performance among sales managers in construction industry and the most factors affected sales performance of sales managers in construction industry. To strengthen this study, the data has been collected through distribution of the questionnaire to the sales managers as the respondents and obtained from journal, reference books, website and published conference articles. Analyzed data were shows, communication skill most sales manager agree the factor affected to improve the sales performance, secondly is experience, competitor and lastly is level of knowledge.